Analysis of the Difficulties of Parents in Accompanying Children with Special Needs at the Elementary School Level during Online Learning in the Covid-19 Pandemic - Fauzi, Ahmad Rizki; Maryanti, Rina; Irawan, Asep Rudi (JASSI ANAKKU, 2020)
The role of parents is needed when students with special needs study from home. However, when accompanying children to learn online, parents find it difficult due to various factors. For this reason, the purpose of this study is to analyze how difficult it is for parents to accompany elementary school children with special needs during online learning. The research method used is descriptive qualitative with the population and the research sample are parents of elementary school students as many as 20 people. The data collection technique used in this research is a survey in the form of a questionnaire, observation notes, and documentation. The results of this study indicate that in general the obstacles for parents in assisting children with special needs to study online at home during the Covid-19 pandemic are the lack of understanding of the material by parents, the difficulty of parents in growing their children's interest in learning, not having enough time to accompany their children because they have to work, parents are impatient in accompanying children while studying at home, parents have difficulties in operating gadgets, and obstacles related to internet service coverage.